Testing the knowledge of Alzheimer's disease via an intervention study among community health service center staff in Jiaxing, China - Ma, Weiwei; Zhu, Liping; Tang, Jiangang; Diao, Wanli; Qian, Liqi; Feng, Xiaoyang; Zhang, Xiaoling (Frontiers in Public Health, 2023)
Objective This study aimed to investigate the knowledge status of Alzheimer's disease (AD) among community health service center (CHSC) staff in Jiaxing, China, and to compare the effects of online with offline training. Methods A total of 763 people from 12 community health service centers were investigated using a self-created general situation questionnaire and the Alzheimer's Disease Knowledge Scale (ADKS). Among the participants, 261 people who were willing to receive training were randomly divided into two groups according to the institution in which they worked to receive online or offline training, respectively. Results The average ADKS score was 19.77, and the awareness rate was 65.92%; the results for every field were as follows: treatment and management (81.32%); life impact (77.76%); disease course (75.23%); assessment and diagnosis (68.94%); risk factors (65.05%); symptoms (57.90%); caregiving (44.06%). Education and profession had impacts on the total ADKS scores (P < 0.05). A total of 261 people participated in the training, and there were significant differences in ADKS scores before and after training (P < 0.05). Before the training, there was no significant difference in ADKS score between the two groups; after the training, either (P > 0.05). There were significant differences in the ADKS scores after training in both groups (P < 0.05). Conclusion Community health service center staff in Jiaxing had limited knowledge of AD, particularly in the “symptom” and “caregiving” dimensions. One instance of training on AD-related knowledge to some degree helped to improve this but still fell short of meeting the national requirements. No significant differences were found between offline and online training effects.